Ta có :\(N=\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^9}\)(1)
\(\Rightarrow3N=1+\frac{1}{3}+...+\frac{1}{3^8}\)(2)
Lấy (2) - (1) ta có :
\(\Rightarrow2N=1-\frac{1}{3^9}\)
\(\Rightarrow N=\frac{1-\frac{1}{3^9}}{2}\)
ta có: \(N=\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+...+\frac{1}{3^9}\)
\(\Rightarrow\frac{1}{3}N=\frac{1}{3^2}+\frac{1}{3^3}+\frac{1}{3^4}+...+\frac{1}{3^{10}}\)
\(\Rightarrow\frac{1}{3}N-N=\frac{1}{3^{10}}-\frac{1}{3}\)
\(\frac{2}{3}N=\frac{1}{3^{10}}-\frac{1}{3}\)
\(N=\frac{\frac{1}{3^{10}}-\frac{1}{3}}{\frac{2}{3}}\)
CHÚC BN HỌC TỐT!!!
\(N=\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+......+\frac{1}{3^9}\)
\(3N=1+\frac{1}{3}+\frac{1}{3^2}+........+\frac{1}{3^8}\)
\(3N-N=1+\frac{1}{3}+\frac{1}{3^2}+......+\frac{1}{3^8}-\left(\frac{1}{3}+\frac{1}{3^2}+\frac{1}{3^3}+.......+\frac{1}{3^9}\right)\)
\(2N=1+\frac{1}{3}+\frac{1}{3^2}+..........+\frac{1}{3^8}-\frac{1}{3}-\frac{1}{3^2}-\frac{1}{3^3}-.....-\frac{1}{3^9}\)
\(2N=1-\frac{1}{3^9}\)
\(N=\frac{1-\frac{1}{3^9}}{2}\)